FITOREMEDIASI TANAH TERCEMAR LOGAM TIMBAL (Pb) MENGGUNAKAN TANAMAN LIDAH MERTUA (Sansevieria trifasciata) DAN JENGGER AYAM (Celosia plumosa) - Ratnawati, Rhenny; Fatmasari, Risna Dwi (Al-Ard: Jurnal Teknik Lingkungan, 2018)
Soil is a very influential medium of human survival. One of the parameters affecting soil quality is heavy metal concentration in soil, especially heavy metal of lead (Pb). High concentrations of Pb in the soil can treated with phytoremediation techniques. The aims of this research are: 1. To investigate the reduction of heavy metal Pb in the soil by phytoremediation, 2. To investigate the effectiveness of plants to absorb heavy metal Pb in the soil, and 3. To investigate the distribution of Pb concentration in the plant parts. The study variables used in this research are species variation of plants Sansevieria trifasciata and Celosia pulmosa. Phytoremediation test of Pb heavy metal contaminated soil was carried out for 4 weeks with sampling time on days 0, 7, 14, 21, and 28. The parameters analyzed of this research is Pb concentrations on soil and plant parts, namely roots, stems, leaf. Physical observations of plants were also carried out to support this research. The results show that the reactor with Sansevieria trifasciata had a higher effectiveness of removal of Pb in 81.08% (112 mg/kg) than Celosia pulmosa in 59.63% (293 mg/kg). The effectiveness of the absorption of Sansevieria trifasciata was higher 70.50% (418 mg/kg) than Celosia pulmosa 52.40% (311 mg/kg). The distribution of Pb concentrations in the plant of Sansevieria trifasciata and Celosia pulmosa is almost the same, with the most concentration being in the root part and at least scattered in the leaves of the plant. Keywords: Celosia pulmosa, Soil, Lead, Phytoremediation, Sanseviera trifasciata.